The information organization for hypermedia applications: the case of MAPEARTE - Ulbricht, Vania Ribas; Pereira, Heloisa Caroline de Souza; Ulbricht, Sergio Murilo; Ferreira, Cláudio Luiz (InfoDesign, 2005)
The purpose of this paper is to point out the importance of the information organization for hypermedia systems, as well as describing the information organization used in the application: MAPEARTE. After the data collection, the information had been grouped and organized by the Conceptual Map tool. This application has two subjects: the first refers to the contemporary visual artists of the city of Florianópolis and the second is a cultural approach about the city where these artists live.